Darbepoetin Alfa in Young Infants With Renal Failure: Single Center Experience, a Case Series and Review of the Literature - Libudzic-Nowak, Anna Maria; Cachat, Francois; Pascual, Manuel; Chehade, Hassib (Frontiers in Pediatrics, 2018)
Background: Anemia treatment in infants with advanced or chronic kidney disease (CKD) represents an important challenge to nephrologists. The use of darbepoetin alfa, a novel erythropoiesis stimulating agent, has largely replaced recombinant human erythropoietin in older children and in adults with CKD. However, studies reporting the use of darbepoetin alfa in infants below 1 year of age are rare. Case presentation: We report the data of three infants with advanced stage kidney failure, aged 1, 4, and 7 months, who were treated with darbepoetin alfa and followed for 18–41 months. Hemoglobin levels increased in all three patients, reaching the target levels of 10.7–12 g/dl by 11, 19, and 22 weeks respectively, without any documented adverse effects. Patients younger than 1 year of age required a larger darbepoetin alfa dosage (ranged from 1.2 to 2.9 μg/kg per month) as compared to older children. A review of the literature found only three studies using darbepoetin alfa successfully in such young infants, with similar dosage and clinical success. Conclusion: In these three patients with advanced kidney disease, darbepoetin alfa was effective in correcting anemia with no observed side effects. It reinforces its potential use in very young patients with advanced CKD.